Meningkatkan Fungsi Kognitif Lansia Dengan Permainan Daur Ulang Berbahan Sampah Plastik - Hilda Mazarina Devi; Ronasari Mahaji Putri; Neni Maemunah (Jurnal Pemberdayaan Masyarakat, 2024)
The elderly experience various aging processes which result in functional decline including cognitive decline. Mild decline in cognitive function is characterized by the occurrence of forgetfulness and if it is severe it will cause senility to the occurrence of Alzheimer's disease, a progressive disease that destroys memory and other important mental functions. Decreased cognitive function can also be caused by a lack of activity in the elderly that involves the brain. So far, processing of plastic waste has been carried out but it is still limited to collecting and reselling it, there has been no attempt to use plastic waste into toys that are beneficial to health and cognitive function. The domino game using plastic bottle caps was created by the team as an activity to support cognitive and social functions for the elderly. Game activities were carried out 12 times for 15 elderly people who were in RT 06 RW 01 Tanjungrejo Village, Sukun District, Malang City. Elderly cognitive function was measured at the beginning and at the end of the activity using the MMSE. The results found are known that although some elderly people experience problems in completing game targets, elderly people who complete game cycles have improved cognitive function. The development and improvement of the appearance of the game set becomes a recommendation for further activities.